(untitled) (Research, Society and Development, 2022)
In Brazil, generally, the sewage sludge is sent to the sanitary landfill, compromising the useful life of the landfills, by occupying the place of other domestic solid waste. In view of the nutrient richness of the sludge, and its agricultural recycling as a technical, economic and environmentally safe alternative, the present work developed a technique for the agricultural recycling of the sewage sludge generated by the sewage treatment plant in the municipality of Igaci, chosen for having its sewage treatment plant recently built (August/2018). The present work sought to calculate the required sludge dosage in agricultural areas, for the main crops used in the municipality. With this, it is intended to carry out the recycling of sewage sludge from the municipality of Igaci, analyzing the necessary dosage of biosolid for each type of culture that can be used in agricultural areas, comparing with other types of organic and chemical fertilizers. This study enables a good management of the sludge from the sewage treatment plant in the municipality of Igaci, favoring the recovery of soils and the optimization of agriculture.